The Effect Of Social Media Promotion Instagram, Word Of Mouth (WOM), And Online Customer Review On Students' Decisions To Take Tutoring In Brits Indonesia Institutions - Arroji, Luthfi; Dewi Ruspitasari, Widi (International Journal of Science, Technology & Management, 2022)
This study aimed to determine the effect of social media promotion Instagram, Word of Mouth (WOM), and Online Customer Review on students' decisions to take tutoring at BRITS Indonesia Institution. The population in this study were all students who had followed the guidance in November 2021. The sample size was 76 respondents; the sampling technique was purposive sampling technique. The type of data used was sourced from primary data and secondary data. Data was collected using observation, questionnaires, and documentation. The technique used to analyze the data was the technique of multiple linear regression analysis. The results showed that the promotion of social media Instagram (X1) had a significant effect on students' decisions to follow tutoring, word of mouth (X2) had a significant effect on students' decisions to follow tutoring, and electronic word of mouth (X3) had a significant effect on students' decisions to follow tutoring study.